Acanthosis nigricans: high prevalence and association with diabetes in a practice-based research network consortium - a PRImary care Multi-Ethnic Network (PRIME Net) study - Kong, Alberta S. (2010)
BACKGROUND: Previous work has established a surprisingly high prevalence of acanthosis nigricans (AN) and its association with increased risk of type 2 diabetes in a Southwestern practice-based research network (PBRN). Our objective was to establish whether this high AN prevalence would be present in other areas. METHODS: We examined prevalence of type 2 diabetes and its risk factors and of AN among patients ages 7–65 seen by one of 86 participating clinicians in a national PBRN consortium, during a one-week data collection period. In a sub-sample of non-diabetic matched pairs with and without AN, we compared fasting glucose, insulin, and lipids. RESULTS: AN was present in 19.4% of 1730 patients, including all age ranges studied. AN was most prevalent among persons with more diabetes risk factors. Patients with AN were twice as likely as those without AN to have type 2 diabetes (35.4% vs. 17.6%, p<.001). In multivariable analysis, the prevalence ratio for diabetes was 2.1 (95% CI = 1.3–3.5) in non-Hispanic whites with AN and 1.4 (95% CI = 1.1–1.7) in minority patients with AN. In a sub-sample of 11 matched pairs, those with AN had higher insulin and insulin resistance. CONCLUSIONS: We found high rates of AN in primary care practices across the country. Patients with AN likely have multiple diabetes risk factors and are more likely to have diabetes.